2018
DOI: 10.21276/aimdr.2018.4.2.ot4
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Perceptions and Knowledge of Strabismus among Pediatrics and Ophthalmology Clinics Attendees in King Abdulaziz University Hospital, Jeddah

Abstract: Background: To assess the knowledge, awareness, and perception about strabismus and related disease dimensions among the parents and companions of children attending the pediatrics and ophthalmology clinic. Methods: A prospective cross-sectional study was carried out between 01 January and 31 July 2017 including the companions of children having strabismus who attended the Pediatrics and Ophthalmology clinics. A semi-structured questionnaire was developed to collect data. Results: The study included 474 compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…is may be due to the messages delivered through radio/TV in a coherent and scientific manner. is was typically consistent with another study in India, Saudi, and Jeddah [21,22,27], in which both radio/TV and the Internet were the reliable sources of knowledge than relatives/friends.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…is may be due to the messages delivered through radio/TV in a coherent and scientific manner. is was typically consistent with another study in India, Saudi, and Jeddah [21,22,27], in which both radio/TV and the Internet were the reliable sources of knowledge than relatives/friends.…”
Section: Discussionsupporting
confidence: 90%
“…is may be due to the difference in the study population who were agrarian and rural dwellers, which made them less aware of strabismus. However, this finding was lower than a study conducted in Jeddah (60-79%), India (94.7%), and Saudi (66.7%) [21,22,27]. is is due to the difference in the study setting since these studies were hospital-based.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The most frequently reported risk factors to develop strabismus are family history and eye refractive errors. However, other works of literature found that hereditary factors and ocular diseases are the most common risk factors for strabismus [18][19].…”
Section: Discussionmentioning
confidence: 95%